Fostering Responsible Citizenship through Effective Preparation for Harmonious Family Relationships (Impact: Journal of Transformation, 2019)
Responsible citizenship is necessary for the development of any society and it can be learned in our homes wherever there are harmonious family relationships. This is based on the premise that the family is the first contact point of any citizen of a nation. Living harmoniously is possible only if the couple who serves as the foundation of the family can handle conflict responsibly. Conflict can be a catalyst for positive change if properly handled. Responsible citizenship requires that citizens know how to handle conflicts which is a direct function of having the right understanding of conflicts; such an understanding can start from the home. This underscores the need for couples themselves to know how to handle conflict before they can help their children. This study embarked on an exploration of the effectiveness of preparation of intending couples for conflict transformation in marriage with a view to understanding the present premarital counseling strategies and possible improvements. This is a descriptive research that used one hundred and twenty (120) selfadministered questionnaires and in-depth interviews of twenty persons. The respondents, all of whose marriages were conducted in Baptist churches located in Port Harcourt, Nigeria, have been married for at least five years and twenty-five years respectively. From the field survey, four major themes were identified; namely, the strategies of premarital counseling, major socio-cultural mindsets that promote conflicts, the role of pastors in handling conflict, and how the Baptist church can help in conflict transformation in marriage. Key findings include major kinds of premarital counseling, the most effective way of preparing people for marriage, the attitude of most intending couples, a comprehensive counseling approach to assist pastors, and negative socio-cultural mindsets that must change. The recommendations include the need for marital mentorship, making one-on-one counseling more appealing to couples through the use of technology.